2021
DOI: 10.3389/fgene.2021.661296
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Volatile Terpenoid Metabolism and Transcriptome Reveals Transcription Factors Related to Terpene Synthase in Two Cultivars of Dendrobium officinale Flowers

Abstract: Dendrobium officinale is a kind of traditional Chinese herbal medicine. Its flowers could be used as health care tea for its aroma flavor and medicinal value. Most recent studies demonstrated that terpenoids are the main components of the aromatic compounds in the flowers, but the biosynthesis of terpenoids is poorly understood in D. officinale. In the experiment, the flowers from two cultivars of D. officinale with different smells were collected. The transcriptome analysis and combined volatile terpenoids de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Accordingly, the similar expression patterns of specific SG synthesis-related genes from RNA-Seq and qRT-PCR results confirmed the validity of our transcriptome analysis results (Figure 7). These transcriptomic analyses suggested the key genes, TFs and pathways in regulating specific metabolism, most of which have been previously reported in terpenoid-enriched plants including Finger Citron [42], Ferula assafoetida [43], Dendrobium officinale [44], as well as stevia [17,45]. The KEGG results clearly indicated that NO 3 − mostly upregulates the pathways relating to secondary metabolism, with "diterpenoid biosynthesis" being the most significant for SGs.…”
Section: Discussionmentioning
confidence: 51%
“…Accordingly, the similar expression patterns of specific SG synthesis-related genes from RNA-Seq and qRT-PCR results confirmed the validity of our transcriptome analysis results (Figure 7). These transcriptomic analyses suggested the key genes, TFs and pathways in regulating specific metabolism, most of which have been previously reported in terpenoid-enriched plants including Finger Citron [42], Ferula assafoetida [43], Dendrobium officinale [44], as well as stevia [17,45]. The KEGG results clearly indicated that NO 3 − mostly upregulates the pathways relating to secondary metabolism, with "diterpenoid biosynthesis" being the most significant for SGs.…”
Section: Discussionmentioning
confidence: 51%
“…In the research, among the top ten volatile metabolites with the highest level in high-scented D. loddigesii (TH), 3-carene (11.87%) had the highest relative content with sweet smell. 3-Carene was a kind of monoterpene, which was identified widely in aromatic constituents of Dendrobium species, such as D. chrysotoxum, D. hancockii, and D. officinale [16,24]. Therefore, we inferred that 3-carene was the base content of floral scent in these Dendrobium species, and it was also the basic constituent of high-scented D. loddigesii aromatic scent.…”
Section: Discussion 41 Identification and Comparison Of Metabolites Between Two Varietiesmentioning
confidence: 97%
“…Terpenes were the dominant components of floral scent in D. chrysotoxum, 15 terpenes were identified as scent components in its flowers [9]. Similarly, the aromatic composition of D. hancockii and D. officinale was mainly terpenes [16]. In the research, among the top ten volatile metabolites with the highest level in high-scented D. loddigesii (TH), 3-carene (11.87%) had the highest relative content with sweet smell.…”
Section: Discussion 41 Identification and Comparison Of Metabolites Between Two Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of metabolomic and transcriptomic analysis has also widely been used to analyze various physiological processes in D. officinale , such as flower development ( He et al, 2020 ), cold acclimation ( Wu et al, 2016 ), stem color ( Zhan et al, 2020 ), salt stress ( Zhang et al, 2021 ), and flower volatile terpenoids ( Li N. et al, 2021 ). Some key factors have been identified to explain why the metabolites were changed, including the key enzymes in the biosynthetic pathway and potential transcription factors ( Li N. et al, 2021 ). For example, the increase in content of delphinidin and quercetin derivatives was responsible for the purple stem of D. officinale and F3H and leucoanthocyanidin dioxygenase ( LDOX ) genes were found to be highly expressed ( Zhan et al, 2020 ).…”
Section: Integration Research Of Multi-omics In Dendrobium Officinalementioning
confidence: 99%